Fast Spectrum Reactors - Waltar, Alan E.; Todd, Donald R.; Tsvetkov, Pavel V.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Fast Spectrum Reactors presents a detailed overview of world-wide technology contributing to the development of fast spectrum reactors. With a unique focus on the capabilities of fast spectrum reactors to address nuclear waste transmutation issues, in addition to the well-known capabilities of breeding new fuel, this volume describes how fast spectrum reactors contribute to the wide application of nuclear power systems to serve the global nuclear renaissance while minimizing nuclear proliferation concerns. Readers will find an introduction to the sustainable development of nuclear energy and the role of fast reactors, in addition to an economic analysis of nuclear reactors. A section devoted to neutronics offers the current trends in nuclear design, such as performance parameters and the optimization of advanced power systems. The latest findings on fuel management, partitioning and transmutation include the physics, efficiency and strategies of transmutation, homogeneous and heterogeneous recycling, in addition to valuable fuel cycle results. The systems section covers fuel pin and assembly design, fuel pin performance, overall systems considerations, and a major chapter on core materials$1 (Bwhere advances in metal fuels and long-life structural capabilities are featured. The safety section includes both traditional safety analysis techniques as well as a perspective on methods to achieve passive safety response. Whereas the bulk of the book is focused on sodium-cooled fast spectrum systems, a final section features gas-cooled and lead-cooled fast reactor systems.s
Part I: Overview -- Sustainable Development of Nuclear Energy and the Role of Fast Spectrum Reactors -- Introductory Design Considerations -- Economic Analysis of Fast Spectrum Reactors -- Part II: Neutronics -- Nuclear Design -- Nuclear Data and Cross Section Processing -- Kinetics, Reactivity Effects and Control Requirements -- Fuel Management -- Part III: Systems -- Fuel Pin and Assembly Design -- Fuel Pin Thermal Performance -- Core Thermal Hydraulics -- Core Materials -- Reactor Plant Systems -- Part IV: Safety -- General Safety Considerations -- Protected Transients -- Unprotected Transients -- Severe Accidents and Containment Considerations -- Part V: Alternate Fast Reactor Systems -- Gas-Cooled Fast Reactors -- Lead-Cooled Fast Reactors.
Keywords: Engineering; Nuclear chemistry; Nuclear physics; Electric engineering; Nuclear engineering; Engineering; Nuclear Engineering; Nuclear Chemistry; Nuclear Physics, Heavy Ions, Hadrons; Energy Technology